Technical regulation in the construction - Tulebekova А.; Zhankina А. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
The system of technical regulation is considered as foundation for the creation of a high construction culture, increasing the competitiveness of the industry in Kazakhstan. Key actions to reform regulatory framework which was established by the government focused on achieving a sustainable balance of economic and social interests of construction participants and consumers. The process of adopting international standards to Kazakhstan soil and construction conditions is gradual. The first step was to adapt foreign technical documentation to the national technological environment. In this way, there were developed appropriate methodologies for assessing conformity to educate builders and designers to develop appropriate training programs, handbooks, and manuals, translation to the Kazakh language, checking the general format of the maintenance of the Eurocodes by comparative calculations, etc. It is important that this process does not contradict the Eurocode relating to any aspects of the requirements in Kazakhstan that are not covered by the Eurocode. The article presents discussions of stages for harmonization and adaptation of Eurocode to Kazakhstan norms.